2013
DOI: 10.1371/journal.pone.0079308
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of Early Serum Creatinine Variations for the Assessment of Kidney Injury in Neonates and Infants with Cardiac Surgery

Abstract: BackgroundChanges in kidney function, as assessed by early and even small variations in serum creatinine (ΔsCr), affect survival in adults following cardiac surgery but such associations have not been reported in infants. This raises the question of the adequate assessment of kidney function by early ΔsCr in infants undergoing cardiac surgery.MethodologyThe ability of ΔsCr within 2 days of surgery to assess the severity of kidney injury, accounted for by the risk of 30-day mortality, was explored retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…41 According to a recent investigation, abrupt postoperative variation of SCr (DSCr) is also a nonsensitive marker because of its delayed rise and lack of differential function between survivors and deceased. 42…”
Section: Traditional Biomarkersmentioning
confidence: 99%
“…41 According to a recent investigation, abrupt postoperative variation of SCr (DSCr) is also a nonsensitive marker because of its delayed rise and lack of differential function between survivors and deceased. 42…”
Section: Traditional Biomarkersmentioning
confidence: 99%
“…S-Cr increases due to acute tubular necrosis and subsequent reduction in glomerular filtration rate (GFR), which results in 50% loss of glomerular function [12][13][14]. Contrarily, The present study showed that ANH-induced hemodilution, which replaces whole blood by 5% HES of 5 ml/kg, does not affect neither s-Cr values nor, consequently, compromise the clinical efficacy of s-Cr.…”
Section: Discussionmentioning
confidence: 56%
“…As a standard surrogate of kidney function, SCr has been used widely in diagnosing and staging AKI despite its limitations. 29,30 Furthermore, relative changes of early SCr also might be one of the indicators for the subsequent development of AKI and poor outcomes. Previous studies have demonstrated the relationship between minimal changes of SCr as predictors for later AKI and overall outcomes in cardiac surgery patients.…”
Section: Discussionmentioning
confidence: 99%